Improvement Design and Application of the F2 Gearbox - Zhang Kun; Hu Jun; Yuan Yongchao; Yu Li; Mao Jizhe; Wu Luji; Li Fuli; Zhang Da (Jixie chuandong)
The F2 gearbox of Angang Steel Company Limited is introduced. Through the improvement design of the gearbox speed ratio,center distance and bearing of this gearbox and the structure strengthen,the performance of the all aspects of gearbox are improved.